Application of Scientific Research of Stone Names in Uzbek Language Importance - Khasanova Barchinoy Kimsanovna (Research Parks Publishing LLC, 2021)
In Sections of onomastics in the article, the basis for naming stones dividing factors and the practical significance of the study of stone names in linguistics thought about. Onomastics is the science that studies famous horses. Onomastics is a branch of lexicology that studies names given to a place, person, plant, natural phenomenon, animal, and so on. Onomastics also studies the phonetic, morphological, word-formation, semantic, etymological, and other aspects of nouns using comparative-historical, structural, genetic, areal, onomastic mapping, and other methods of linguistics.